Avaliação da adequabilidade do ambiente geológico do local de disposição final de resíduos sólidos da Região de Integração Guamá - Castanhal/Pará - PINHEIRO, Adson Caxias (2019)
Lack of solid waste management is becoming a problem for managers of Brazilian municipalities. This is happening due to the large expansion of urban areas and, consequently, due to the increase in consumption. Improper accumulation of solid waste has been increasing constantly, therefore, they are thrown thousands of tons of "waste" daily landfill known as "dumps". This is a reality experienced not only by the Castanhal city as well as by most municipalities. As a result, this study aimed to evaluate the suitability of the geological environment of the final disposal site for solid waste and the management of solid waste in Region of Guama integration, focusing on the city of Castanhal. Specifically, this work is to present the way the city is managing solid waste and confronting with the legal instruments and requirements and technical standards. The methodology chosen in the research is classified as exploratory, descriptive, beyond the technical methodology of letters overlay to construct the letter of the areas suitable for disposal landfill, with the universe the city of Castanhal. The main results indicate that the collection of waste is not made appropriately. Landfills, much of the Pantanal as of May 1 are already on the edge, with the need for new strategies to remedy the problem. The suitability of the sites currently used for disposal of solid waste is discussed. The suitability map for landfill deployment of Castanhal Municipality is presented. Keywords: Amazon,